Treatment times in breast cancer patients receiving neoadjuvant vs adjuvant chemotherapy: Is efficiency a benefit of preoperative chemotherapy? - Nicole M. Melchior; Darren B. Sachs; Gabrielle Gauvin; Cecilia Chang; Chihsiung E. Wang; Elin R. Sigurdson; John M. Daly; Allison A. Aggon; Shelly B. Hayes; Elias I. Obeid; Richard J. Bleicher (Cancer Medicine)
Abstract Background/Objective Delays in times to surgery, chemotherapy, and radiotherapy impair survival in breast cancer patients. Neoadjuvant chemotherapy (NAC) confers equivalent survival to adjuvant chemotherapy (AC), but it remains unknown which approach facilitates faster initiation and completion of treatment. Methods Women ≥18 years old with nonrecurrent, noninflammatory, clinical stage I‐III breast cancer diagnosed between 2004 and 2015 who underwent both surgery and chemotherapy were reviewed from the National Cancer Database. Results Among 155 606 women overall, 28 241 patients received NAC and 127 365 patients received AC. NAC patients had higher clinical T and N stages (35.8% T3/4 vs 4.9% T3/4; 14.4% N2/3 vs 3.7% N2/3). After adjusting for stage and other factors, NAC patients had longer times to begin treatment (36.1 vs 35.4 days adjusted, P = .15), and took significantly longer to start radiotherapy (240.8 vs 218.2 days adjusted, P < .0001), and endocrine therapy (301.6 vs 275.7 days adjusted, P < .0001). Unplanned readmissions (1.2% vs 1.7%), 30‐day mortality (0.04% vs 0.01%), and 90‐day mortality (0.30% vs 0.08%) were all low and clinically insignificant between NAC and AC. Conclusion Compared to patients receiving AC, those receiving NAC do not start treatment sooner. In addition, patients receiving NAC do not complete treatment faster. Although there are clear indications for administering NAC vs AC, rapidity of treatment should not be considered a benefit of giving chemotherapy preoperatively.